Characterizing Adult Cochlear Supporting Cell Transcriptional Diversity Using Single-Cell RNA-Seq: Validation in the Adult Mouse and Translational Implications for the Adult Human Cochlea - Hoa, Michael; Olszewski, Rafal; Li, Xiaoyi; Taukulis, Ian; Gu, Shoujun; DeTorres, Alvin; Lopez, Ivan A.; Linthicum Jr., Fred H.; Ishiyama, Akira; Martin, Daniel; Morell, Robert J.; Kelley, Matthew W. (Frontiers in Molecular Neuroscience, 2020)
Hearing loss is a problem that impacts a significant proportion of the adult population. Cochlear hair cell loss due to loud noise, chemotherapy and aging is the major underlying cause. A significant proportion of these individuals are dissatisfied with available treatment options which include hearing aids and cochlear implants. An alternative approach to restore hearing would be to regenerate hair cells. Such therapy would require recapitulation of the complex architecture of the organ of Corti, necessitating regeneration of both mature hair cells and supporting cells. Transcriptional profiles of the mature cell types in the cochlea are necessary to can provide a metric for eventual regeneration therapies. To assist in this effort, we sought to provide the first single-cell characterization of the adult cochlear supporting cell transcriptome. We performed single-cell RNA-Seq on FACS-purified adult cochlear supporting cells from the LfngEGFP adult mouse, in which supporting cells express GFP. We demonstrate that adult cochlear supporting cells are transcriptionally distinct from their perinatal counterparts. We establish cell type-specific adult cochlear supporting cell transcriptome profiles, and we validate these expression profiles through a combination of both fluorescent immunohistochemistry and in situ hybridization co-localization and qPCR of adult cochlear supporting cells. Furthermore, we demonstrate the relevance of these profiles to the adult human cochlea through immunofluorescent human temporal bone histopathology. Finally, we demonstrate cell cycle regulator expression in adult supporting cells and perform pathway analyses to identify potential mechanisms for facilitating mitotic regeneration (cell proliferation, differentiation, and eventually regeneration) in the adult mammalian cochlea. Our findings demonstrate the importance of characterizing mature as opposed to perinatal supporting cells.